Language diversity in urban landscapes: An econometric study - Laura Onofri; Paulo A. L. D. Nunes; Jasone Cenoz; Durk Gortner (Fondazione Eni Enrico Mattei (FEEM), 2008)
This multidisciplinary study adopts econometric analysis for investigating how different characteristics determine the choice of the language used in the signs of a shopping street. We work with a dataset containing about 200 observations collected in the main shopping streets of the cities of Donostia (Spain) and Ljouwert (The Netherlands). The results corroborate the important assumption that multilingualism and the choice of the language (even in a street sign) is an individual and a social preference. Therefore, understanding individuals' linguistic preference structures is preliminary to the target and design of proper linguistic and social policies.
Keywords: C01; R20; Z13; 330; Linguistic Diversity; Street Sign; Probit Model; Linguistic Landscape; Sprache; Baskisch; Spanisch; Niederländisch; Sprachpolitik; Kultursoziologie; Public Choice; Schätzung; Spanien; Niederlande